Pengaruh Kualitas Manajemen Kesiswaan Terhadap Tingkat Kedisiplinan Siswa Tingkat Wustha Di Madrasah Diniyah - Fauzi, Muhammad Irfan; Umam, Muh Khotibul (STAI Denpasar Bali, 2024)
Student management is a process of guidance or coaching for students starting from initial entry to graduation from an educational institution in order to guide students so that participating in teaching and learning activities can run optimally and also so that in the process students can comply with the regulations that have been implemented and minimize student for committing violations. The research that will be carried out aims to determine the influence of the quality of student management on the level of discipline of Wustho level students at Madrasah Diniyah Al Amiriyyah Pondok Pesantren Darussalam Blokagung Banyuwangi for the 2021/2022 Academic Year. Student management is one of the most urgent school management because it is directly related to students regarding guidance to them for the effectiveness of teaching and learning activities. This research method uses quantitative methods. This type of research will use quantitative descriptive. The data collection technique uses a questionnaire which will be tested for validity and reliability. To find out whether there is a significant influence between student management on the quality of discipline of Wustho level students at Madrasah Diniah Al Amiriyyah Darussalam Islamic Boarding School Blokagung Banyuwangi for the 2021/2022 Academic Year using the Pearson product moment formula.